The homewreckers [compact disc, unabridged] : a novel - Andrews, Mary Kay, 1954- (Macmillan Audio, 2022)
Hattie Kavanaugh went to work helping clean up restored homes for Kavanaugh & Son Restorations at eighteen; married the boss's son at twenty; and was only twenty-five when her husband, Hank, was killed in a motorcycle accident. Broken hearted, but determined to continue the business of their dreams, she takes the life insurance money, buys a small house in a gentrifying neighborhood, flips it, then puts the money into her next project. But that house is a disaster and a money-loser, which rocks her confidence for years to come. Then, Hattie gets a once-in-a-lifetime opportunity: star in a beach house renovation reality show called The Homewreckers, cast against a male lead who may be a love interest, or may be the ultimate antagonist. It's a question of who will flip, and who will flop, and will Hattie ever get her happily-ever-after.